Bacon’s “Envy”: An Evaluation of Punctuation - Muhammad Waqar Ali (University of Chitral Journal of Linguistics and Literature, 2018)
Punctuation plays a pivotal role in enhancing comprehensibility of a text. It notonly abolishes ambiguity from the text but also adorns the individual style of theauthor. This paper analyses Bacon’s essay “Envy” evaluating the aberrant use ofpunctuation to understand its impact on holistic comprehension of the essay. Baconhas deviated in some punctuation marks in different situations. Most deviationsoccur in the use of the comma and the semicolon. The least deviations occur in theuse of the period. Two explanations may be inferred from the analysis: First, whatseems to be deviant in this regard was normal in his time; second, he deviates onpurpose to make the long, complex sentence clear and easy for the reader.